Determining Ergonomic Smartphone Forms With High Grip Comfort and Attractive Design. (February 2019) - Lee, Songil; Kyung, Gyouhyung; Yi, Jihhyeon; Choi, Donghee; Park, Sungryul; Choi, Byeonghwa; Lee, Seungbae
Objective: The authors aimed to identify ergonomic smartphone forms by investigating the effects of hand length, four major smartphone dimensions (height, width, thickness, and edge roundness), and smartphone mass on grip comfort and design attractiveness. Background: Despite their potential effect on grip comfort and design attractiveness, the dimensions specified above have never been simultaneously considered in a study investigating smartphone gripping. Method: Seventy-two young individuals participated in a three-stage study. Stage 1 determined the ranges of the four smartphone dimensions suitable for grip comfort and identified the strengths of their influences. Stage 2 investigated the effects of width and thickness (determined to have the greatest influence) on grip comfort and design attractiveness. Mock-ups of varying masses were fabricated using the dimensions determined during the first two stages to investigate the effect of mass on grip comfort and design attractiveness in Stage 3. Results: Phone width was found to significantly influence grip comfort and design attractiveness, and the dimensions of 140 × 65 (or 70) × 8 × 2.5 mm (height × width × thickness × edge roundness) provided high grip comfort and design attractiveness. The selected dimensions were fit with a mass of 122 g, with masses in the range of 106–137 g being comparable. Conclusion: The findings of this study contribute to ergonomic smartphone design developments by specifying dimensions and mass that provide high grip comfort and design attractiveness. Application: The dimensions and mass determined in this study should be considered for improving smartphone design grip comfort and attractiveness.